Arab-Iranian Relations Since the Arab Uprisings (Taylor & Francis, 2024)
Unlike most writing on Arab-Iran relations, which looks at specific episodes and specific countries, this book, taking a long term view, assesses the overall dynamics of the relationship, discussing in particular how far religion or politics drives the relationship. It argues that although Iran asserts that religion is a key factor underpinning a coherent approach to international relations, in fact what turns out to be the key factor is the politics of particular circumstances and Iran's specific interests. The book considers Iran's differing reactions to the Arab uprisings of 2011 onwards, showing that while Iran supported the uprisings in some countries it sided with repressive governments in other countries. The book also examines Iran's reaction to its own outbreak of popular discontent in 2009 which was controlled by what has been considered as severe repression and explores how Iran is viewed by ordinary people in different Arab countries.
English
Keywords: Arab Uprisings,Arab Iranian Relations,Iranian Foreign Policy,Islamic Revolution,Islamic Republic,Islamic Awakening,Muslim Brotherhood,Muslim World,Political Islam,Syrian Uprising,Assad Regime,Arab Public Opinion,Pahlavi Script,Israel Hezbollah War,Umm Al Qura,Vice Versa,Favourability Ratings,Persian Language,Arab Public,Arab Perception,Iran's Role,Sassanian Empire,Quds Force,Arab Political System,NATO's Involvement,Politics,Religion,Relationship,Arab Uprisings,Arab,Iran; thema EDItEUR::G Reference, Information and Interdisciplinary subjects::GT Interdisciplinary studies::GTM Regional / International studies; thema EDItEUR::J Society and Social Sciences::JB Society and culture: general::JBS Social groups, communities and identities::JBSL Ethnic studies; thema EDItEUR::J Society and Social Sciences::JH Sociology and anthropology::JHB Sociology::JHBC Social research and statistics